The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/e20110860
|View full text |Cite
|
Sign up to set email alerts
|

Refined Multiscale Fuzzy Entropy to Analyse Post-Exercise Cardiovascular Response in Older Adults With Orthostatic Intolerance

Abstract: Orthostatic intolerance syndrome occurs when the autonomic nervous system is incapacitated and fails to respond to the demands associated with the upright position. Assessing this syndrome among the elderly population is important in order to prevent falls. However, this problem is still challenging. The goal of this work was to determine the relationship between orthostatic intolerance (OI) and the cardiovascular response to exercise from the analysis of heart rate and blood pressure. More specifically, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Moreover, the similarity between BP and HR entropy measures, in relation to frailty status, suggests that these measures may provide complementary information, as has been previously reported [ 54 ], and as such a univariant approach (i.e., the assessment of one of these measures) may be sufficient for clinical use. Input parameters and implementation of ApEn and SampEn calculations were based on recommendations for similar physiological data from previous studies ( m = 2 (also reported in Appendix B m = 3, 4) [ 14 , 35 ]; r = 0.15 (SampEn) [ 37 , 38 ], optimum calculated [0 to 0.6] (ApEn) [ 14 ]; N > 200 [ 24 , 35 ]); however, a consensus with regards the optimal methodologies to use, as well as normative age- and sex-adjusted reference values, would be required for widespread clinical adoption. Further work is necessary to establish the prognostic implications of entropy measures vis-à-vis other clinical markers (e.g., for the prediction of mortality and other adverse health events).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the similarity between BP and HR entropy measures, in relation to frailty status, suggests that these measures may provide complementary information, as has been previously reported [ 54 ], and as such a univariant approach (i.e., the assessment of one of these measures) may be sufficient for clinical use. Input parameters and implementation of ApEn and SampEn calculations were based on recommendations for similar physiological data from previous studies ( m = 2 (also reported in Appendix B m = 3, 4) [ 14 , 35 ]; r = 0.15 (SampEn) [ 37 , 38 ], optimum calculated [0 to 0.6] (ApEn) [ 14 ]; N > 200 [ 24 , 35 ]); however, a consensus with regards the optimal methodologies to use, as well as normative age- and sex-adjusted reference values, would be required for widespread clinical adoption. Further work is necessary to establish the prognostic implications of entropy measures vis-à-vis other clinical markers (e.g., for the prediction of mortality and other adverse health events).…”
Section: Discussionmentioning
confidence: 99%
“…SampEn [ 17 ] was calculated as however, in this instance, does not count self-matches. For SampEn, an r of 0.15 was selected, in line with previous recommendations for similar physiological data [ 37 , 38 ]. To assess the effects of data stationarity on entropy measures, we calculated ApEn and SampEn for both the original raw and transformed data.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, m (embedding dimension; the length of the data segment being compared) was set to 2, as this has been shown to provide good statistical validity for SampEn measurements, especially for biological data [20,21]. An r (similarity criterion) of 0.15 was selected in line with previous recommendations for similar physiological data [22,23]. To assess the effects of data stationarity on entropy measures, SampEn was calculated for both the original and transformed one-minute data.…”
Section: Entropy Analysismentioning
confidence: 99%
“…Please refer to the literatures [20], [21] for the details. The relevant research have shown that RCMFE is more reliable than MFE technique and has widely used in varying fields [12], [21], [34]. However, the shorten-data problem still exists unavoidably in the procedure.…”
Section: Backgrounds a Multiscale Fuzzy Entropymentioning
confidence: 99%